Investigation and experiment of radar systems in unmanned arial vehicles - SzeToh, Benjamin YongJian (2013)
Presented in this report, it is an investigation into testing practices and the possible method to show how much noise is produced. As high noise levels could bring to personal health risks and significant amount of noise induced hearing loss. For all the possible techniques of measurement testing will be using the Hewlett Packard HP35670A Dynamic Signal Analyzer, as it analysis the signal for low frequency component. There will be two case studies are presented in this report, one of it will be the evaluation on noise produces in the UAV while the another case study will be on the evaluation on noise produces in the hairdryer. Both of the case studies will be using the possible techniques of acoustic measurement which will be taken and the testing technique will be examined and studied in relation to the position of the place of the individual UAV and a hairdryer, in which dominating the sound level.